1997
DOI: 10.1002/art.1780400419
|View full text |Cite
|
Sign up to set email alerts
|

Low‐level increases in serum C‐reactive protein are present in early osteoarthritis of the knee and predict progressive disease

Abstract: Objective. To examine the role of low-grade inflammation in the etiology and progression of early osteoarthritis (OA) of the knee.Methods. We used a new, high-sensitivity, automated monoclonal antibody immunoassay for the classic acute-phase protein, C-reactive protein (CRF'), in serum. Anteroposterior radiographs of the knee with weight bearing were obtained on 845 women (ages 44-67) on entry into a population-based study of OA in Chingford, North London. In those defined radiologically as "cases," the knee r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
183
2
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 350 publications
(200 citation statements)
references
References 12 publications
14
183
2
1
Order By: Relevance
“…The mechanism through which estrogen decreases cytokine induced VCAM-1 production by inhibition of NF-κβ, AP-1 and GATA transcription factors. [30] In this study the serum level of CRP was also found significantly high in postmenopausal women with symptoms of knee osteoarthritis as compared to control which is in consistent with the study of Spector et al who reported modestly but significant increase of CRP level in women with early stage of knee osteoarthritis [14] . CRP is an acute phase protein, which reflects a measure of the acute-phase response.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The mechanism through which estrogen decreases cytokine induced VCAM-1 production by inhibition of NF-κβ, AP-1 and GATA transcription factors. [30] In this study the serum level of CRP was also found significantly high in postmenopausal women with symptoms of knee osteoarthritis as compared to control which is in consistent with the study of Spector et al who reported modestly but significant increase of CRP level in women with early stage of knee osteoarthritis [14] . CRP is an acute phase protein, which reflects a measure of the acute-phase response.…”
Section: Discussionsupporting
confidence: 91%
“…[9][10][11][12] ] C-reactive protein (CRP) serving as a marker for systemic inflammation, several studies showing a relationship between serum CRP levels and osteoarthritis of the knee. [13][14][15] Although, CRP is not taken as an optimal marker for inflammation in osteoarthritis; other putative markers have been associated with some osteoarthritis phenotypes. These include proinflammatory cytokines, cell adhesion molecules and adiponectin.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, biochemical parameters such as C-reactive protein (CRP), muscle creatine phosphokinase (CPK mm) and aldolase-A were recorded separately followed by the methods of other researchers [26][27][28]. The biochemical parameters were done from blood/serum, collected individually for all males and females.…”
Section: Estimation Of Biochemical Parameters From Blood/serummentioning
confidence: 99%
“…We did not found any relation between age and positive CRP in our patients that's similar to Pearle et al 22 studies, this is against many epidemiological studies. 25 Several studies have reported relationships between CRP and various features of KOA, in Spector et al 26 and Sturmer et al 24 studies a population based, cross sectional study observed increased CRP values in women with radiographically defined knee OA. In contrast, our results showed no significant relationship between C-reactive protein and sex.…”
Section: Methodsmentioning
confidence: 99%